The Nebraska Nomogram for Autograft Planning (NNAP) a surgical planning tool for ipsilateral rotational autokeratoplasty - Collin Asheim; Ashok Puri; Helen Song; Brian Armstrong; Sam Navon; Ronald Krueger (npj Digital Medicine)
Abstract Corneal opacification impairs vision and may necessitate surgery. Ipsilateral rotational autokeratoplasty (IRA) offers an alternative to allograft keratoplasty for treating localized opacities within the visual axis while minimizing risks. A novel digital twin software was developed to assess IRA feasibility and optimize surgical planning. Using corneal imaging, pachymetry, topography, and corneal white to white measurements, the software dynamically adjusts surgical variables, including trephine size and placement, graft rotation, and curvature matching, without manual calculations. This tool provides precise graft placement parameters to maximize the amount of clear cornea in the visual axis. Retrospective use on a past IRA case confirmed its accuracy and significantly reduced planning time. A patient undergoing IRA with this software achieved successful graft placement, improved visual function, and no post-operative complication or rejection. By reducing cognitive load and standardizing planning, this software enhances IRA procedures, making them more efficient and standardized.